IMPORTANCE OF GEOGRAPHY EDUCATION IN TERMS OF SUSTAINABLE DEVELOPMENT TRAINING - Mehmet Fatih KAYA (Fırat University, 2019)
In our day, our unconscious interventions to the nature in conjunction with development of science and technology caused ecosystem balances and let global scale problems arise. In this epoch, where the humanity damages the life space severely, raising nature-sensitive in